Transient Left Bundle Branch Block During the Recovery Period of a Stress Test - Efrat, Mazor Dray; Yuval, Konstantino; Reuben, Ilia (Journal of Hypertension and Cardiology, 2014)
Exercise-dependent complete left bundle branch block is a rare entity.We present a case in which this phenomenon was demonstrated during the recovery period of a stress test. To the best of our knowledge such an observation has not been previously described.
Keywords: left bundle branch block; stress test; recovery period Exercise-dependent complete left bundle branch block is a rare entity.